Pakistan - Rural Factor Markets : Policy Reforms for Growth and Equity - World Bank (Washington, DC, 2013)
Accelerating rural economic growth and reducing rural poverty requires a comprehensive strategy built on sound analysis covering all major aspects o f the rural economy including agricultural output markets, input markets (seeds, fertilizer, extension), factor markets (land, water, labor and credit), the rural non- farm economy, and targeted interventions. This report focuses on one aspect o f this complex puzzle - rural factor markets. It builds on earlier work on output and input markets, and anticipates future analytical work on the rural non-farm economy and other key aspects o f the rural economy. The report identifies the main factor market inefficiencies in rural Pakistan, provides estimates of their impact in terms of efficiency and equity, and suggests policy measures to improve the functioning of these markets, increase rural incomes and help reduce rural poverty. In presenting the results, each factor is discussed in turn, drawing on descriptions of institutional constraints and statistical analysis of recent household survey data. Key new findings include quantitative estimates of the importance of linkages across factor markets and the impact of factor market inefficiencies on agricultural output and revenues. In addition, the report shows that for the 61 percent of rural poor households that do not cultivate crops (agricultural laborers and non-farm households), expanding output of major crops may not be sufficient to significantly raise their incomes, even with substantial multiplier effects on the rural non-agricultural economy.